2015
DOI: 10.1021/acs.joc.5b01676
|View full text |Cite
|
Sign up to set email alerts
|

Multicomponent Reaction of Z-Chlorooximes, Isocyanides, and Hydroxylamines as Hypernucleophilic Traps. A One-Pot Route to Aminodioximes and Their Transformation into 5-Amino-1,2,4-oxadiazoles by Mitsunobu–Beckmann Rearrangement

Abstract: Synthetically useful aminodioximes are prepared via a novel three-component reaction among Z-chlorooximes, isocyanides, and hydroxylamines by exploiting the preferential attack of isocyanides to nitrile N-oxides via a [3 + 1] cycloaddition reaction. The results of quantum mechanical studies of the reaction mechanism are also discussed. Furthermore, the one-pot conversion of aminodioximes to 1,2,3-oxadiazole-5-amines via Mitsunobu-Beckmann rearrangement is reported for the first time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 43 publications
(35 reference statements)
0
7
0
Order By: Relevance
“…In particular, Isocyanide-based Multicomponent Reactions (IMCRs) [1][2][3][4], have been proven to be an ideal tool to provide in one single step medium-complexity molecular skeletons, usually accessible only via a multistep approach. Most of MCR chemistry is performed with isocyanides and is related to the Ugi reaction [5,6], a four-component transformation (4CR) described in 1959 by Professor Ivar Ugi. In the reaction, an acid component, like a carboxylic acid, reacts with an oxo-component (a ketone or an aldehyde), a primary amine, and an isocyanide.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Isocyanide-based Multicomponent Reactions (IMCRs) [1][2][3][4], have been proven to be an ideal tool to provide in one single step medium-complexity molecular skeletons, usually accessible only via a multistep approach. Most of MCR chemistry is performed with isocyanides and is related to the Ugi reaction [5,6], a four-component transformation (4CR) described in 1959 by Professor Ivar Ugi. In the reaction, an acid component, like a carboxylic acid, reacts with an oxo-component (a ketone or an aldehyde), a primary amine, and an isocyanide.…”
Section: Introductionmentioning
confidence: 99%
“…The formation of the carbonyl is accompanied by the loss of the thiocyanate unit. Water attacks the C=N carbon in 11 c leading to the formation of a diol and an imine in 11 d , further rearrangement results in the final product 11 .…”
Section: Resultsmentioning
confidence: 99%
“…34 After optimization of the reaction conditions, we obtained the aminodioxime 44 in 72% yield just by mixing (Z)phenylchloroxime (14), pentyl isocyanide (25), and hydroxylamine (43) in dichloromethane at room temperature, using sodium hydrogen carbonate as the base (Scheme 9). 35…”
Section: Scheme 8 Two-step Synthesis Of 12-benoxazole-3-carboxamidesmentioning
confidence: 99%
“…Results showed that mechanism C was the most energetically favorable in comparison with mechanisms A and B, and with the energy barrier of the direct attack of the third nucleophile to the nitrile N-oxide species. 35…”
mentioning
confidence: 99%